2021
DOI: 10.1007/s12282-021-01235-y
|View full text |Cite
|
Sign up to set email alerts
|

Practical approach to prevent COVID-19 infection at breast cancer screening

Abstract: Background The novel coronavirus disease 2019 (COVID-19) undermines the benefits of cancer screening. To date, no study has identified specific infection control methods. We aimed to provide practical methods for COVID-19 risk reduction during breast cancer screening mammography (MMG) by examining an overview of potential contamination routes of aerosols and possible risks for patients and health care providers. Methods Computational fluid dynamics (CFD) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(17 reference statements)
2
3
0
Order By: Relevance
“…1 ). This finding is consistent with our previous report 9 . Furthermore, the movement of aerosols was modeled under the assumption that a patient coughs, and it was found that the number of aerosols deposited on the physician was comparable with that resulting from normal patient expiration, although small aerosols diffused widely throughout the room (Fig.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…1 ). This finding is consistent with our previous report 9 . Furthermore, the movement of aerosols was modeled under the assumption that a patient coughs, and it was found that the number of aerosols deposited on the physician was comparable with that resulting from normal patient expiration, although small aerosols diffused widely throughout the room (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…To investigate how to efficiently ventilate indoor spaces, it is important to understand air flow as a function of humidity, which has a strong effect on aerosol properties. We have previously investigated and reported infection control methods in medical settings 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of this theoretical study clearly show that aerosols emitted from a patient's mouth or nose in an examination room, where masks must be removed, are greatly affected by the airflow in the room, and the risk of their deposition on the physician and elsewhere in the room cannot be neglected (Figure 2). This finding is consistent with our previous report (8). Furthermore, the movement of aerosols was modeled under the assumption that a patient coughs, and it was found that the number of aerosols deposited on the physician was comparable with that resulting from normal patient expiration, although small aerosols diffused widely throughout the room (Figure 3).…”
Section: Discussionsupporting
confidence: 91%
“…We have previously investigated and reported infection control methods in medical settings. (8) Indoor healthcare facilities attract both infected people and patients at high risk of serious illness. Various evidence shows that strict precautions against droplet exposure, such as wearing personal protective equipment and social distancing, are insufficient, and measures to prevent exposure to aerosols are not always well considered.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have investigated aerosol removal by forced ventilation [7] and air-conditioning systems that control aerosol behavior [8] in consultation rooms. However, it may be difficult to replicate these methods in existing consultation rooms.…”
Section: Introductionmentioning
confidence: 99%